Teacher's Use and Students’ Perception on Oral Corrective Feedback in English Morning Program (EMO) - Ivan, Moh Nawawi; Hakim, Lukman (Journal of English Language and Education, 2024)
Speaking is a crucial skill for effective communication, especially for learners using a non-native language. In this study, we investigate the types of oral corrective feedback (OCF) used by English teachers and students' perceptions of when this feedback should be given. The research employs a descriptive qualitative design, focusing on 2 English teachers and 35 students from seven majors at SMK Bhakti Mulia Pare, Kediri, specifically in the English Morning Program (EMO). Data were collected through observations, interviews, and questionnaires. The questionnaire, comprising 15 items, used a Likert Scale to gauge students' feelings about OCF, their perceptions of it, and how they believe it should be delivered. The study finds that Teacher A predominantly used recasts, while Teacher B utilized both recasts and repetition. Recasts involve incorporating the content of the incorrect utterance into a corrected version. Additionally, the questionnaire results indicate that over 68.1% of students agreed with the feedback provided by their teachers. The findings suggest that oral corrective feedback is beneficial and can enhance students' speaking competence.